2021
DOI: 10.3390/rs13173437
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Volume Extraction of Citrus reticulate Blanco cv. Shatangju Trees Using UAV Image-Based Point Cloud Deep Learning

Abstract: Automatic acquisition of the canopy volume parameters of the Citrus reticulate Blanco cv. Shatangju tree is of great significance to precision management of the orchard. This research combined the point cloud deep learning algorithm with the volume calculation algorithm to segment the canopy of the Citrus reticulate Blanco cv. Shatangju trees. The 3D (Three-Dimensional) point cloud model of a Citrus reticulate Blanco cv. Shatangju orchard was generated using UAV tilt photogrammetry images. The segmentation eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In this research, UAV, MA and MLS point clouds were compared to assess the canopy size parameters of vertical trained vines (Vitis vinifera L.). Manual measurements of the canopy volumes were not taken due to several uncertainties, such as the identification of the vine canopy boundary and being subjective and dependent on the person taking the measure itself as well as on the tool or strategy used to assess the canopy height and thickness [60,61]. Moreover, some researchers have found that manual measurements over-estimate the canopy thickness of about 30% with respect to LiDAR ones [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, UAV, MA and MLS point clouds were compared to assess the canopy size parameters of vertical trained vines (Vitis vinifera L.). Manual measurements of the canopy volumes were not taken due to several uncertainties, such as the identification of the vine canopy boundary and being subjective and dependent on the person taking the measure itself as well as on the tool or strategy used to assess the canopy height and thickness [60,61]. Moreover, some researchers have found that manual measurements over-estimate the canopy thickness of about 30% with respect to LiDAR ones [62].…”
Section: Discussionmentioning
confidence: 99%
“…UAV technology was widely used to assess canopy volumes and it was shown to be a quick and low-cost solution compared to ground measurements of canopy size parameters [50, 60,[64][65][66][67][68][69]. The UAV point cloud processing led to similar results in canopy volume values concerning other research, but they used a voxel method [70] and an alphashape approach [38,71].…”
Section: Discussionmentioning
confidence: 99%
“…A considerable amount of research on orchard canopy information focus on the identification and counting of individual trees ( Morales et al., 2018 ; Cheng et al., 2020 ; Qi et al., 2021 ). In fact, due to geometric features of plant canopies can offer relevant indicators, individual canopy-related features interested farmers but the most accurate estimations for canopies all mostly based on destructive and costly labour-intensive manual measurements ( Gower et al., 1999 ; Jonckheere et al., 2004 ; Ma et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apple trees are cultivated worldwide and more than 87 million tons of apples are produced each year (FAOSTAT, 2019). Fertile planting land and high-quality orchard management are necessary to ensure the stable and increased production of apples (Qi et al, 2021). The volume and exterior structure of the canopy of apple trees are significant markers for determining their growth and biological characteristics (Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Gülci (2019) built a 3D canopy model using UAV-based photogrammetry technology to estimate the number, height, and canopy coverage of trees. Based on oblique photogrammetry, Qi et al (2021) combined deep learning-based segmentation to obtain the 3D point cloud of a single fruit tree and estimated the volume of the tree canopy. UAV-based oblique photogrammetry with point cloud data processing has become the most popular method for estimating individual tree volume.…”
Section: Introductionmentioning
confidence: 99%